Humidity sensor and method of manufacturing the same

CN117538388BActive Publication Date: 2026-10-30FUQING BRANCH OF FUJIAN NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311505947.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-13
Publication Date
2026-10-30
Estimated Expiration
2043-11-13

AI Technical Summary

Technical Problem

该体系涂覆性较差,湿敏材料无法与电极形成有效粘附,难以制得高可靠性的湿度传感器

Benefits of technology

[0035]1.本发明提供了一种用于高湿度(湿度>90%)下连续检测的湿度传感器的制备方法,基于多官能团的高活性缩合剂与导电高分子材料,通过两步涂覆法,先将多官能团的高活性缩合剂均匀涂覆在电极表面,形成交联剂层。然后再将导电高分子溶液涂覆在交联剂层上,使导电高分子溶液可将交联剂层原位溶解并迅速发生原位交联反应,由于交联反应是在电极表面原位进行,从而有效避免了多官能团的高活性交联剂在与导电高分子材料在本体溶液中迅速扩散发生的非均相交联反应以及生成不均匀交联产物的问题。这种在电极表面原位形成具有均匀且致密交联网络结构的湿敏层,并且与电极具有良好涂覆性的特点,有效解决了目前高分子类湿度传感器无法在高湿度条件下长期稳定检测的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117538388B_ABST
    Figure CN117538388B_ABST
Patent Text Reader

Abstract

The application provides a humidity sensor and a preparation method thereof. A conductive polymer solution is coated on an electrode surface which has been previously distributed with a multi-functional high-activity condensing agent, so that the conductive polymer and the multi-functional high-activity condensing agent are crosslinked on the electrode surface in situ, and a humidity-sensitive layer with a compact crosslinked structure and good adhesion to the electrode is obtained. The humidity sensor prepared by the method can continuously monitor humidity of >90%. In addition, the method has the advantages of simple operation and automatic production. The prepared humidity sensor has the characteristics of flexibility, miniaturization and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of humidity sensor manufacturing technology, specifically to a humidity sensor capable of continuous humidity detection under conditions of relative humidity > 90% and its manufacturing method. Background Technology

[0002] Humidity is one of the most important environmental factors affecting people's daily lives and production, and its accurate measurement and control are of great significance. Continuous monitoring of humidity in environments with relative humidity >90% has important applications in the medical and health industry, including clinical trial rooms / cabinets, intensive care units, clinical investigation laboratories, blood centers, testing and sample cabinets; in the pharmaceutical industry, it includes drug warehouses, pharmacies, veterinary clinics, medicine cabinets / boxes, and vaccine cabinets / boxes; and in agriculture, it is crucial for seed cultivation. For example, in intensive care units, active humidification devices used on patients with artificial airways need to maintain a relative humidity level >90% for several days after surgery to ensure airway patency. Continuous monitoring of humidity levels in the patient's upper respiratory tract is essential for maintaining normal airway function. Furthermore, these applications require humidity sensors to be flexible and miniaturized for compact integration with other components. Finally, the fabrication and signal readout of the devices must also consider low cost.

[0003] Existing humidity sensors are insufficient for continuous monitoring of humidity levels far exceeding those of ordinary atmospheric environments. Current humidity sensors can only operate briefly in high humidity (>90%, ~5 minutes) conditions, and sensors that meet the requirement of continuous operation under >90% humidity are lacking. Common humidity-sensitive materials include inorganic nanomaterials, organic molecules, organic polymers, and high-molecular-weight materials. Among these, humidity sensors based on ceramics and metal oxides lose their detection capability after absorbing moisture, as the moisture is adsorbed within the micropores of the ceramics and metal oxides and cannot be spontaneously removed. Therefore, these sensors lose their detection capability after a short period of operation (~5 minutes) under high humidity and require heating to dehydrate and restore their sensing performance. Organic molecules and organic polymers are unsuitable for use in high humidity environments because they dissolve. High-molecular-weight humidity-sensitive materials have advantages such as ease of processing, diverse synthesis methods, ease of compounding with other materials, and low cost. However, under high humidity conditions, polymer chains are prone to segment dissolution / migration / relaxation, leading to poor long-term stability of the sensors. Methods such as blending, interpenetrating network structures, grafting, and crosslinking of moisture-sensitive polymers can alleviate the long-term stability problems of humidity sensors caused by polymer chain dissolution / migration / relaxation. Among these, chemical crosslinking of moisture-sensitive polymers is an effective way to improve the long-term robustness of devices. For example, H. He et al. reported crosslinking of a tannic acid-based amine conductive polymer moisture-sensitive material—polyethyleneimine—via a Michael addition reaction (patent application number: 202310734541.6; Sensor. Actuat. B-Chem. 2023, 393, 134194), obtaining a crosslinked moisture-sensitive polymer material; then, the crosslinking product was applied to the electrode surface to obtain a humidity sensor. The moisture sensor exhibited good stability in its moisture sensing capability when stored under atmospheric conditions. In the above technical solutions, to ensure the coatability of the moisture-sensitive material system and to achieve good adhesion between the final moisture-sensitive film and the electrode, the crosslinking reaction between the crosslinking agent and the conductive polymer material is a homogeneous reaction system. In other words, the reaction between the crosslinking agent and the humidity-sensitive material under sample preparation conditions is relatively mild, so that the final crosslinked product is a homogeneous solution to meet the requirements of subsequent electrode coating. To meet the above conditions, a mild crosslinking system is required to avoid a rapid crosslinking reaction between the crosslinking agent and the humidity-sensitive material under sample preparation conditions, which would cause precipitation from the solution. However, this results in a loose crosslinked network of the obtained humidity-sensitive polymer, and the resulting humidity sensor cannot operate continuously in environments with humidity levels greater than 90%.

[0004] In contrast, using highly reactive small-molecule condensing agents with multifunctional groups as crosslinking reagents to crosslink humidity-sensitive polymers can yield a dense crosslinked network, effectively resisting the swelling problem of humidity-sensitive materials in high-humidity environments. However, crosslinking humidity-sensitive polymers with highly reactive small-molecule condensing agents with multifunctional groups reacts rapidly at room temperature, forming a heterogeneous system and precipitating the crosslinked network in solution. This system has poor coatability, and the humidity-sensitive material cannot effectively adhere to the electrode, making it difficult to fabricate a highly reliable humidity sensor. Overall, there are no reports on the development of humidity sensors, especially humidity sensors suitable for continuous monitoring in high-humidity environments, based on the dense crosslinked system obtained by the crosslinking reaction of humidity-sensitive polymers with highly reactive small-molecule condensing agents with multifunctional groups. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention provides a humidity sensor and its fabrication method. By coating a conductive polymer solution onto an electrode surface pre-distributed with a highly reactive multifunctional condensing agent, a cross-linking reaction occurs in situ between the conductive polymer and the highly reactive multifunctional condensing agent on the electrode surface, forming a densely cross-linked humidity-sensitive layer with good adhesion on the electrode surface. The humidity sensor prepared by this method has the ability to continuously detect humidity under conditions of >90% humidity.

[0006] The first aspect of this invention provides a method for manufacturing a humidity sensor, comprising the following steps:

[0007] (1) A highly active condensing agent with multiple functional groups is coated on the electrode to form a crosslinking agent layer on the electrode surface;

[0008] (2) A conductive polymer solution is coated on a crosslinking agent layer and reacted in situ with a highly active condensing agent with multiple functional groups to form a dense crosslinked humidity-sensitive layer, thereby obtaining the humidity sensor; wherein the conductive polymer and the condensing agent are bonded by an acid-amine condensation reaction.

[0009] Furthermore, the electrode is an interdigitated electrode structure or a serpentine electrode structure.

[0010] Furthermore, the substrate of the electrode is preferably a flexible substrate, including but not limited to a polymer film.

[0011] Furthermore, the electrode has a planar structure or a porous structure, more preferably a metal or carbon array with a porous structure, in order to increase the contact area between the humidity-sensitive layer and the electrode, thereby improving the sensitivity of the sensor.

[0012] Furthermore, when the electrode has a porous structure, the average pore diameter of the electrode is preferably 1-10 μm, and the ratio of the surface area of ​​the pores in the electrode to the area occupied by the corresponding electrode is preferably 20:1-80:1.

[0013] Furthermore, the electrode can be prepared using electrode processing techniques such as laser carbonization, sputtering, electroplating, and vapor deposition.

[0014] Furthermore, before preparing the crosslinking agent layer on the electrode surface, the electrode surface is first subjected to a hydrophilic treatment; the hydrophilic treatment is selected from one or more of silane coupling agent modification treatment, plasma treatment, and strong acid acidification treatment; the hydrophilic treatment makes the contact angle of the electrode surface less than 90°, so that the humidity-sensitive layer and the electrode can be bonded by chemical bonding or van der Waals forces, thereby improving the bonding force between the electrode and the humidity-sensitive layer, so that the humidity sensor prepared has a good bonding force between the humidity-sensitive layer and the electrode under high humidity test conditions, avoiding the detachment between the humidity-sensitive layer and the electrode due to moisture absorption / dehydration when entering / leaving a high humidity environment.

[0015] Further, in step (1), the highly active multifunctional condensing agent is one or more of a small molecule acid and its halogenated derivatives. The multifunctional group refers to a molecule containing ≥2 functional groups of acid radicals and haloo groups. This type of highly active multifunctional crosslinking condensing agent has a low activation energy for crosslinking reactions with conductive polymers, and can form a macromolecular insoluble precipitate when mixed with conductive polymer materials in solution. Upon contact at the electrode interface, it reacts in situ at room temperature to form a dense crosslinked structure.

[0016] Furthermore, the small molecule acid is an acid with a molecular weight of <1000.

[0017] Furthermore, the selection of multifunctional small molecule acids includes, but is not limited to, oxalic acid, tartaric acid, malic acid, citric acid, and phytic acid. Their halogenated derivatives are selected from products of fluorine, chlorine, and bromine.

[0018] Further, in step (1), the concentration of the condensing agent is 0.01%-1%; preferably, the condensing agent is a water-soluble reagent.

[0019] Further, in step (1), the ratio of the number of reactive functional groups in the crosslinking agent layer to the specific surface area of ​​the electrode is preferably 0.1-5 nmol / mm². 2 .

[0020] Further, in step (1), the condensing agent solution is coated on the electrode surface by spraying, dripping or spin coating; more preferably, it is coated by spraying so that the atomized droplets come into contact with the electrode, ensuring that a small amount of liquid can come into uniform contact with the electrode, thereby ensuring that the crosslinking agent is uniformly deposited on the electrode surface.

[0021] Furthermore, in step (1), the drying process is carried out at room temperature and pressure, for example, solvent removal is carried out at 25°C and one atmosphere to ensure that the solvent can evaporate slowly.

[0022] Further, in step (2), the conductive polymer material is a polymer containing abundant amino or amine groups. Preferably, it is one or more of polyethyleneimine and its derivatives, including but not limited to branched polyethyleneimine, polyethyleneimine-polylactic acid-glycolic acid, benzoic acid-midified polyethyleneimine and its derivatives.

[0023] Further, in step (2), the concentration of the conductive polymer solution is 1%-10%, and more preferably, the conductive polymer is a water-soluble reagent.

[0024] Further, in step (2), the conductive polymer solution is coated onto the electrode surface by spraying, dripping or spin coating; more preferably, it is coated by spraying so that the atomized droplets come into contact with the electrode, ensuring that the moisture-sensitive polymer solution can come into uniform contact with the crosslinking agent layer pre-coated on the electrode.

[0025] In some preferred embodiments, the solvent used to dissolve the conductive polymer material is the same as the solvent used to dilute the crosslinking agent, so that the solvent in the sprayed conductive polymer solution can redissolve the crosslinking agent in situ and then undergo an in-situ crosslinking reaction with the conductive polymer.

[0026] This invention employs a two-step coating method. First, a highly active multifunctional condensing agent is uniformly coated onto the electrode surface to form a crosslinking agent layer. Then, a conductive polymer solution is coated onto the crosslinking agent layer. This allows the conductive polymer solution to dissolve the crosslinking agent layer in situ and rapidly induce an in-situ crosslinking reaction. Since the crosslinking reaction occurs in situ on the electrode surface, it effectively avoids the heterogeneous crosslinking reaction caused by the rapid diffusion of the highly active multifunctional crosslinking agent with the conductive polymer material in the bulk solution, thus preventing the formation of uneven crosslinking products.

[0027] Further, in step (2), during the crosslinking reaction, the molar ratio of the reactive functional groups of the conductive polymer to the condensing agent is 1:10. -4 ~10 -2 The aforementioned reactive functional groups refer to active functional groups that can participate in cross-linking reactions.

[0028] Further, in step (2), the reaction temperature of the crosslinking reaction is 20-35℃, and the reaction time is 5min-24hr; the preferred reaction temperature of the crosslinking reaction is 25℃.

[0029] Furthermore, in step (2), the humidity-sensitive layer is a continuous film layer, and the thickness of the humidity-sensitive layer is preferably 0.5-10 μm.

[0030] This invention ensures effective crosslinking and the formation of a continuous film by controlling the coating amount of a highly active multifunctional condensing agent on the electrode and its feeding ratio with the conductive polymer. If the coating area of ​​the highly active multifunctional condensing agent on the electrode is small, or the feeding ratio with the conductive polymer is too low, the purpose of effective crosslinking will not be achieved. Under high humidity conditions, the uncrosslinked polymer will swell or even dissolve. Conversely, excessive crosslinking will result in too low carrier concentration or mobility in the humidity-sensitive layer, leading to excessively high signal noise, resistance, or impedance, making humidity detection impossible. Therefore, to achieve continuous monitoring capability of the sensor in high humidity environments (>90%) while ensuring the signal-to-noise ratio of the sensor detection signal, it is necessary to rationally control the proportion of the pre-coated highly active condensing agent layer and the subsequently coated conductive polymer that undergoes in-situ crosslinking reaction with it. Furthermore, as mentioned above, the amount of highly reactive condensing agent used in this patent is far lower than that of conventionally used mild condensing agents.

[0031] Furthermore, in the humidity sensor prepared by this invention, the response time and sensitivity of the sensor are limited by the thickness of the cross-linked humidity-sensitive layer: the thinner the appropriately cross-linked humidity-sensitive layer, the faster the response speed; however, if the number of charge carriers in the polymer between the electrodes is too small, the resistance or impedance of the device will be too high, which is not conducive to detection; while if the humidity-sensitive layer is too thick, water molecules will have difficulty diffusing into the interior of the humidity-sensitive layer, thereby reducing the sensitivity of the sensor and lengthening the response time. Therefore, in order to balance the response capability and sensitivity of the sensor, the thickness of the humidity-sensitive layer needs to be controlled within a suitable range, such as 0.5-10 μm.

[0032] A second aspect of the present invention provides a humidity sensor prepared by the preparation method described in the first aspect.

[0033] Furthermore, the humidity sensor can continuously detect humidity under conditions of >90% humidity.

[0034] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0035] 1. This invention provides a method for fabricating a humidity sensor for continuous detection under high humidity (humidity > 90%) conditions. Based on a multifunctional, highly active condensing agent and a conductive polymer material, a two-step coating method is used. First, the multifunctional, highly active condensing agent is uniformly coated onto the electrode surface to form a crosslinking agent layer. Then, a conductive polymer solution is coated onto the crosslinking agent layer, allowing the conductive polymer solution to dissolve the crosslinking agent layer in situ and rapidly undergo an in-situ crosslinking reaction. Because the crosslinking reaction occurs in situ on the electrode surface, it effectively avoids the heterogeneous crosslinking reaction that occurs when the multifunctional, highly active crosslinking agent rapidly diffuses with the conductive polymer material in the bulk solution, as well as the problem of generating uneven crosslinking products. This method, which forms a humidity-sensitive layer with a uniform and dense crosslinked network structure in situ on the electrode surface and has good coating properties with the electrode, effectively solves the problem that current polymer-based humidity sensors cannot achieve long-term stable detection under high humidity conditions.

[0036] 2. The humidity sensor manufacturing method provided by the present invention is simple and can be automated. The humidity sensor is flexible and miniaturized and can be easily integrated with other components. More importantly, the humidity sensor can continuously monitor humidity environments with >90% humidity, filling the gap in humidity sensors for continuous operation under such humidity conditions. Attached Figure Description

[0037] Figure 1 The Bode impedance diagram of the sensor is obtained under the test conditions of 30°C and relative humidity of 95% and 80% in Example 1.

[0038] Figure 2 The complex plane impedance diagram of the sensor is shown in Example 1 under the test conditions of 30°C and relative humidity of 95% and 80%.

[0039] Figure 3 The Bode impedance diagram of the newly prepared sensor in Example 2 is shown at a test temperature of 30°C and different relative humidities.

[0040] Figure 4 The impedance value of the sensor prepared in Example 2 was obtained by storing it at 95% humidity for 24 hours, testing it at a temperature of 30°C, and testing it at a fixed frequency of 10Hz under different relative humidity conditions.

[0041] Figure 5 The impedance response behavior of the sensor prepared in Example 2 was continuously monitored under 95% and 80% humidity conditions after being stored at 95% humidity for 24 hours.

[0042] Figure 6The impedance response behavior of the sensor prepared in Example 2 was continuously monitored under 95% and 80% humidity conditions after being stored at 95% humidity for 60 days.

[0043] Figure 7 This is a photograph taken after the crosslinking product in Comparative Example 1 was soaked in deionized water for 24 hours.

[0044] Figure 8 This is a photograph of the white precipitate obtained after reacting phytic acid solution with branched polyethyleneimine solution for 5 seconds in Comparative Example 2. Detailed Implementation

[0045] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0046] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. However, the embodiments described are not intended to limit the present invention.

[0047] Example 1

[0048] Gold interdigitated electrodes were prepared by electroplating, with a width, spacing, and interdigitation index of 3 mm, 0.5 mm, and 10 electrodes, respectively. Malic acid was diluted with deionized water to a 0.1 wt% solution, and this solution was sprayed onto the electrodes using a spraying device, controlling the malic acid spraying amount per unit area to be 1 nmol / mm². 2 The coated electrode was air-dried in an atmospheric environment, then baked on a hot plate at 50°C for 30 minutes. After cooling the electrode to room temperature, 10 wt% branched polyethyleneimine was further sprayed onto the same area. The amount of branched polyethyleneimine sprayed per unit area was controlled so that the molar ratio of ammonium ions in the branched polyethyleneimine to acid ions in the pre-sprayed malic acid was 1:10. -3 Then, let the coated electrodes air dry in an atmospheric environment and bake them on a hot plate at 50°C for 30 minutes.

[0049] Figure 1The Bode impedance diagrams of the sensor are shown under test conditions of 30°C and relative humidity of 95% and 80%. The diagrams show that at the same test frequency, the sensor impedance decreases with increasing humidity. This is because as humidity increases, more molecules are adsorbed into the humidity-sensitive layer, leading to protonation of the layer and the generation of more free radicals, resulting in a decrease in impedance. Furthermore, under high humidity conditions, the sensor's impedance frequency response decreases with increasing frequency, indicating a high cross-linking density that significantly reduces the free ion content in the humidity-sensitive polymer. Therefore, the sensor's impedance response is primarily capacitive. Higher frequencies result in lower impedance. This behavior differs significantly from existing humidity-sensitive polymers whose impedance behavior under high humidity is mainly controlled by ion transport, indirectly confirming that the highly active multifunctional cross-linking agent used in this invention achieves rapid and effective cross-linking even at small doses. Figure 2 The complex plane impedance diagram of the sensor is further shown, and the results are consistent with the analysis above.

[0050] Example 2

[0051] Porous carbon electrodes were fabricated using laser carbonization technology. A 125 μm thick polyimide film was cut into 5 mm × 5 mm strips, and carbon interdigitated electrodes were prepared using carbon dioxide laser carbonization. The laser processing parameters were: speed 10 mm / s; operating power 0.15 W; linear electrode pairs were fabricated with an electrode spacing of 0.10 mm. The surface area of ​​the resulting carbon electrodes was 50 mm² per unit projected area. 2 / mm. Phytic acid was diluted with deionized water to a 0.1 wt% solution. Using a spraying device, the 0.1 wt% phytic acid solution was sprayed onto the electrode, controlling the amount of phytic acid sprayed per unit area to be 3 nmol / mm. 2 The coated electrode was air-dried in an atmospheric environment, then baked on a hot plate at 50°C for 30 minutes. After cooling the electrode to room temperature, 10 wt% branched polyethyleneimine was sprayed onto the same area, controlling the amount of branched polyethyleneimine sprayed per unit area to be such that the molar ratio of ammonium ions in the branched polyethyleneimine to acid ions in the pre-sprayed phytic acid was 1:10. -3 Then, let the coated electrodes air dry in an atmospheric environment and bake them on a hot plate at 50°C for 30 minutes.

[0052] Figure 3 The Bode impedance diagrams of the sensor are shown at a test temperature of 30°C under different relative humidity conditions. Because the carbon electrode obtained by laser carbonization has a high specific surface area, it is beneficial to increase the contact area between the humidity-sensitive layer and the electrode, thereby improving the sensor's sensitivity. Therefore, its humidity detection range is wider than that of a metal planar electrode, and it can be used to test humidity values ​​in the range of 45%-95%. Figure 4The figure shows the impedance values ​​of the sensor at a fixed frequency of 10Hz under different relative humidity conditions at a test temperature of 30℃ after being stored at 95% humidity for 24 hours. As can be seen from the figure, it can still be used for detection under different humidity levels after 24 hours of storage at high humidity. This is significantly different from humidity sensors based on ceramics and metal oxides, where moisture is adsorbed in the micropores of the ceramics and metal oxides after absorption and cannot be spontaneously removed. Figure 5 and Figure 6 The impedance response behavior of the sensor under continuous monitoring at 95% and 80% humidity conditions during a 60-day test period is shown.

[0053] Comparative Example 1

[0054] Using a spraying device, a 0.1 wt% phytic acid solution was sprayed onto the glass slide, controlling the amount of phytic acid sprayed per unit area to be 1 nmol / mm². 2 The coated glass slides were air-dried in an atmospheric environment, then baked on a hot plate at 50°C for 30 minutes. After cooling the glass slides to room temperature, 10 wt% branched polyethyleneimine was sprayed onto the same area. The amount of branched polyethyleneimine sprayed per unit area was controlled so that the molar ratio of ammonium ions in the branched polyethyleneimine to carboxylic acid ions in the pre-sprayed phytic acid was 1:10. -3 The coated glass slide was then air-dried in an atmospheric environment and baked on a 50°C hot plate for 30 minutes. The slide was then tilted and immersed in deionized water. The photograph taken after 24 hours of immersion is shown below. Figure 7 As shown in the figure, the branched polyethyleneimine cross-linked with phytic acid is a continuous film-like substance. After being soaked in water for 24 hours, it maintains its continuous film-like state without obvious swelling or deformation.

[0055] Comparative Example 2

[0056] Add 10 wt% branched polyethyleneimine solution dropwise to a 0.1 wt% phytic acid solution, such as... Figure 8 As shown, upon the addition of branched polyethyleneimine solution to phytic acid solution, a visible white precipitate appears within a short time (<5s), and this precipitate does not disperse after stirring with a stirring rod. The results indicate that a small-molecule, multifunctional, highly active crosslinking agent can rapidly undergo a crosslinking reaction with amino-rich conductive polymers in the liquid phase, producing a crosslinked product with a high molecular weight and a dense network structure. This white precipitate lacks coating properties and cannot form good adhesion to porous or planar electrodes.

[0057] The embodiments described above are merely preferred examples to fully illustrate the present invention, and the scope of protection of the present invention is not limited thereto. Equivalent substitutions or modifications made by those skilled in the art based on the present invention are all within the scope of protection of the present invention. The scope of protection of the present invention is defined by the claims.

Claims

1. A method for preparing a humidity sensor, characterized in that, Includes the following steps: (1) A highly active condensing agent with multiple functional groups is coated on the electrode to form a crosslinking agent layer on the electrode surface; The highly active condensing agent with multiple functional groups is one or more of small molecule acids and their halogenated derivatives; the multiple functional groups are defined as having ≥2 anions and haloan anions in one molecule. (2) A conductive polymer solution is coated onto a crosslinking agent layer, and then subjected to an in-situ crosslinking reaction with a highly active condensing agent containing multiple functional groups to form a crosslinked humidity-sensitive layer, thereby obtaining the humidity sensor; wherein the conductive polymer and the condensing agent are bonded through an acid-amine condensation reaction; the conductive polymer is one or more of polyethyleneimine and its derivatives; the molar ratio of the reactive functional groups of the conductive polymer and the condensing agent is 1:

10. -4 ~ 1:10 -2 .

2. The preparation method according to claim 1, characterized in that, Multifunctional small molecule acids include one or more of oxalic acid, tartaric acid, malic acid, citric acid, and phytic acid.

3. The preparation method according to claim 1, characterized in that, The ratio of the number of reactive functional groups in the crosslinking agent layer to the electrode area is 0.1-5 nmol / mm². 2 .

4. The preparation method according to claim 1, characterized in that, The electrode is selected from porous electrodes or planar electrodes.

5. The preparation method according to claim 1, characterized in that, In step (2), the crosslinking reaction is carried out at a temperature of 20-35°C for 5 min-24 hr.

6. The preparation method according to claim 1, characterized in that, In step (2), the thickness of the humidity-sensitive layer is 0.5-10 μm.

7. A humidity sensor prepared by the preparation method according to any one of claims 1-6.

Citation Information

Patent Citations

  • Humidity sensor and preparation method thereof

    CN116840302A

  • Humidity-sensitive element and method of manufacturing the same

    JP2002267627A